Reconstructing Cosmic Harmony: Singer, Indigenous Justice, and the Legal Pluralism of Forest Fire Governance among the Dayak Ngaju - Nuredy Irwansyah Putra; Wahyu Yun Santoso (Jurnal Dinamika Hukum, 2026)
Recurring forest and land fires (Karhutla) in Central Kalimantan reveal not merely an environmental emergency, but a structural failure of Indonesia’s state-centered environmental law to deliver effective and socially legitimate ecological justice. This article critically examines how the Dayak Ngaju customary legal system challenges the dominance of punitive–administrative fire governance through singer sanctions and community-based adjudication, which frame forest fires as violations of collective ecological order rather than isolated criminal acts. Employing a socio-legal approach, the study combines doctrinal analysis of national environmental law with contextual examination of indigenous legal practices to expose the tension between state law and living customary law in the resolution of forest fires. The analysis demonstrates that, while state law prioritizes criminal liability and regulatory compliance, Dayak Ngaju customary law operates through restorative accountability, material compensation, and community responsibility aimed at restoring ecological balance. This article argues that the marginalization of indigenous legal mechanisms is not a neutral administrative choice, but a source of ecological injustice that perpetuates ineffective fire governance. Its central contribution lies in advancing a critical legal pluralism framework that repositions Dayak Ngaju customary law as a legally operative system capable of correcting the limitations of state environmental law. By foregrounding indigenous legal sovereignty as an analytical claim rather than a cultural footnote, this study offers a normative critique of Indonesia’s environmental governance and proposes a more context-sensitive pathway toward ecological justice grounded in legally recognized pluralism.